Fracture fixation in the hand and wrist: A 16-year population-based study of 56 163 patients from the Swedish National Patient Register - Viktor Schmidt; Elsa Pihl; Cecilia Mellstrand Navarro; Michael Axenhus (PLoS ONE, 2025)
Hand and wrist fractures are among the most common orthopaedic injuries, with a growing trend toward surgical treatment. However, large-scale data on regional variations and treatment trends remain limited. This population-based study analyses the incidence, trends, and regional variations in hand and wrist fracture fixation with plates and screws in Sweden from 2008 to 2023, with predictive modelling for future trends. A total of 56,163 patients aged ≥15 years underwent fixation (code NDJ69). Southern regions, including Skåne and Halland, had the highest fixation rates (>100/100,000), while northern areas like Norrbotten had significantly lower rates (<20/100,000). Women ≥65 years had the highest incidence. Predictive models indicate a continued increase in procedures, particularly among women aged ≥65, through 2035. These findings highlight regional disparities and the ongoing shift towards surgical treatment in older populations, emphasizing the need for optimized treatment strategies to ensure equitable access to care.